(untitled) (Academicia Globe: Inderscience Research, 2024)
This article addresses the importance of meticulous oral hygiene for orthodontic patients seeking a healthy and beautiful smile. Braces and aligners create areas susceptible to plaque buildup, potentially leading to cavities and gum disease. To combat this, the article equips readers with effective brushing and flossing techniques, including the use of angled brushes, floss threaders, water flossers, and interdental brushes. Dietary modifications are emphasized, recommending soft foods and avoiding sugary treats that can damage braces. Mouthwash is presented as a beneficial supplement, not a replacement, for brushing and flossing. The importance of regular dental checkups for monitoring progress and maintaining gum health is highlighted. Finally, the article underscores the collaborative effort between patients, orthodontists, and dentists in achieving a successful outcome.